2010
DOI: 10.1002/bit.22994
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an artificially selected GS‐NS0 variant with increased resistance to apoptosis

Abstract: Heterogeneity in gene expression and phenotypic traits is an inherent feature within the "clonal" cell lines used for biopharmaceutical production. This feature can allow the selection of cell lines with improved phenotypes and adaptation to growth under preferential conditions to improve productivity or provide a platform to study the molecular basis of improved characteristics. A repeated process of extended batch culture of a recombinant antibody producing GS-NS0 myeloma cell line generated a stable variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The batch cultures started with a high fraction of cells in the G 1 /G 0 phase, which rapidly left this state in order to join the proliferating population. Soon after, glutamate deprivation occurred at around 50 h of culture, whereby atf5 upregulation peaked (50% higher) suggesting that glutamate deprivation is among the first factors that introduce metabolic stress, in agreement with previous results [5]. The upregulation of atf5 triggered the upregulation of bcl-2 (which followed at around 90 h).…”
Section: Resultssupporting
confidence: 90%
“…The batch cultures started with a high fraction of cells in the G 1 /G 0 phase, which rapidly left this state in order to join the proliferating population. Soon after, glutamate deprivation occurred at around 50 h of culture, whereby atf5 upregulation peaked (50% higher) suggesting that glutamate deprivation is among the first factors that introduce metabolic stress, in agreement with previous results [5]. The upregulation of atf5 triggered the upregulation of bcl-2 (which followed at around 90 h).…”
Section: Resultssupporting
confidence: 90%
“…However, the mechanism underlying these improvements has not yet been elucidated. We believe that using a transcriptomic approach, such as the pathway-focused polymerase chain reaction (PCR) array, which has proven to be useful in a similar study [47], we can elucidate the connections between mTOR, cell growth, and productivity. Thus, this study initially employed two recombinant CHO cell lines with a 17.4-fold difference in specific productivity to study the differential expressions of genes related to the mTOR signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Such regulation is repressed and autophagy is induced in the presence of nutrient starvation or the macrolide antibiotic rapamycin (sirolimus, Abeliovich, 2004). Recent studies have also shown that autophagy plays an important survival role in higher eukaryotes (Browne and Al-Rubeai, 2011;Kim et al, 2009) and it has been suggested to be important in developing improved eukaryotic strains for biotechnology applications (Zustiak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%